2017
DOI: 10.1038/ncomms14248
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of prostate-specific antigen levels identifies novel loci independent of prostate cancer

Abstract: Prostate-specific antigen (PSA) levels have been used for detection and surveillance of prostate cancer (PCa). However, factors other than PCa—such as genetics—can impact PSA. Here we present findings from a genome-wide association study (GWAS) of PSA in 28,503 Kaiser Permanente whites and 17,428 men from replication cohorts. We detect 40 genome-wide significant (P<5 × 10−8) single-nucleotide polymorphisms (SNPs): 19 novel, 15 previously identified for PSA (14 of which were also PCa-associated), and 6 previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 83 publications
4
57
0
Order By: Relevance
“…One possible solution for this issue is reanalysis of existing GWAS data. Indeed, a focused survey of the literature reveals that when re-analyses included the X chromosome, novel and biologically relevant genetic findings were detected for diabetes mellitus type 2 [145], prostate cancer [146], and orofacial clefts [147]. To the best of our knowledge, such reanalyses have not yet been conducted for ASD and ADHD.…”
Section: Adhd In Scasmentioning
confidence: 99%
“…One possible solution for this issue is reanalysis of existing GWAS data. Indeed, a focused survey of the literature reveals that when re-analyses included the X chromosome, novel and biologically relevant genetic findings were detected for diabetes mellitus type 2 [145], prostate cancer [146], and orofacial clefts [147]. To the best of our knowledge, such reanalyses have not yet been conducted for ASD and ADHD.…”
Section: Adhd In Scasmentioning
confidence: 99%
“…This drive has led to over 40 genome wide association studies (GWAS) executed over the last decade which have identified approximately 170 common variants to the disease . At the molecular level, these variants can be categorized as hereditary, sporadic or epigenetic, whereby, the latter two can overlap and some noteworthy ones are listed in Table while others are discussed elsewhere …”
Section: Causes For Prostate Cancer Disparitiesmentioning
confidence: 99%
“…75 At the molecular level, these variants can be categorized as hereditary, sporadic or epigenetic, whereby, the latter two can overlap and some noteworthy ones are listed in Table 2 while others are discussed elsewhere. [75][76][77][78][79][80][81][82][83] The common thread observed in these studies is that more than 90% of these investigations are conducted in MEA. As a result, significant strides have been made in the design of serum and urine diagnostic biomarkers, whereby some are currently clinically applicable as mentioned earlier and these were recently reviewed in Sharma et al 86 Some include (a) the noncoding RNA, PCA3 that is believed to be overexpressed in 95% of PCa cases in MEA, 76,86 presents in high levels in some men but is unaccompanied by malignancy meanwhile additional studies confirmed an association of this biomarker in Chinese men 87,88…”
Section: Molecular Studiesmentioning
confidence: 99%
“…In recent years, genome-wide association studies (GWAS) have become a powerful strategy for the detection of variation in different traits based on high throughput SNP platforms. It has been widely used in humans (Hindorff et al, 2009 ; Lauc et al, 2010 ; Hoffmann et al, 2017 ) and domestic animals (Petersen et al, 2013 ; Kominakis et al, 2017 ). In pigs, many GWAS have been performed on various economically important traits, including immune traits (Luo et al, 2012 ; Ponsuksili et al, 2016 ), meat quality traits (Casiró et al, 2017 ; Verardo et al, 2017 ), and structural soundness traits (Fan et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%